Investigating the fatigue performance of conventional reinforced concrete CRTS III ballastless track structures using a fatigue damage constitutive model - Song, Li; Shi, Jiarui; Wu, Jun; Cui, Chenxing; Liu, Ran; Yu, Zhiwu (Engineering structures, 2024)
Compared to prestressed track structures, the mechanisms underlying fatigue degradation in conventional reinforced concrete track structures under high-cycle train loads remain elusive. This paper introduces a finite element model for CRTS (China Railway Track System) III slab ballastless track. In this model, fatigue damage constitutive relationships for both concrete and reinforcement are incorporated as material subroutines. The study focuses on investigating the fatigue characteristics of composite plate structures, which consist of track slabs and self-compacting concrete (SCC). An accelerated calculation method for high-cycle fatigue issues is utilized. Several key findings emerge from this study. First, the onset of fatigue cracks is observed on the lower surface of the SCC, directly beneath the applied load. These cracks tend to propagate laterally from the most critical location toward the slab edge. Second, a significant interrelationship exists between material fatigue degradation and stress redistribution. Traditional decoupled fatigue analysis methods are likely to overestimate the rate of fatigue evolution at critical points. Third, increasing the stiffness of geotextiles can partially optimize stress distribution within the track structures, thereby extending the time to initial cracking. •The fatigue damage constitutive equations for concrete and reinforcement were subjected to secondary development.•Developed an accelerated algorithm for efficiently solving the high cycle fatigue problem in ballastless track structures.•Revealed the evolution of fatigue damage and stress distribution in ballastless track structures.•Predicted the fatigue life of ballastless track structures.